Allometric Equation for Pinang (Areca catechu) Biomass and C Stocks - Cahyo Prayogo; Rika Ratna Sari; Degi Harja Asmara; Subekti Rahayu; Kurniatun Hairiah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Pinang nut (Areca catechu L.) is a major agroforestry crops in Papua with high economic value. This study developed allometric equations for estimating Pinang biomass on the basis of stem diameter and height by destructive sampling inagroforestry systems. Aboveground biomass was measured and linked to plant stem diameter at various heights (0.13 and 130 cm above the ground) and plant height. The resultant equation was used for biomass estimates in various agroforestry systems with Pinang trees, with total of 18 plots differentiated in bottom, middle and upper slope positions. As expected for palm trees, plant height is a better predictor (Y = 0.816 H1.42; R2 = 0.89) of biomass than stem diameter, with equal results for diameter measurements at 13 or 130 cm height (Y = 0.0689 D2.59; R2 = 0.74). Best results were for an equation combining diameter and plant height: Y = 0.03883*H*D1.2; R2 = 0.96. Agroforestry systems on the upper slopes had the highest carbon stocks (38.8 Mg ha-1) than the middle and lower slopes (25.9 and 22.5 Mg ha-1, respectively). Aboveground carbon stocks of Pinang in study area ranged from 0.96 to 20.9 kg C tree-1 with an average of 10.1 kg C tree-1.